The Use of Response Tokens In Waiting for Godot by Samuel Beckett (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
This study discusses the use of response tokens in Waiting for Godot written by Samuel Beckett. Specifically, it examines kinds and the functions of response tokens uttered by the main characters. This research uses descriptive approach to obtain rich description and to understand response tokens in Waiting for Godot. The data were taken form Vladimir's and Estragon's utterances. The key findings suggest that the types of response tokens in the drama are single response token, response token preceding expanded response, premodified response token, negative token and doublet and also triplet token. Meanwhile, the functions of response token include the function of continuers, acknowledgement, newsmarker, change-of-activity, assessement and brief question token.